2016
DOI: 10.1007/s00270-016-1394-2
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Angioplasty for Complete Membranous Obstruction of Suprahepatic Inferior Vena Cava: Long-Term Results

Abstract: Percutaneous transluminal angioplasty for a complete membranous obstruction of the suprahepatic inferior vena cava is safe and effective, and the long-term results are excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Membranous occlusion of veins is rare and mostly reported in the suprahepatic inferior vena cava (IVC), resulting in hepatic venous outflow obstruction. Angioplasty by balloon dilations can be a safe and effective treatment for membranous occlusion of IVC (5)(6)(7)(8). Our patient was also relieved by balloon dilation of SCV and recovered successfully.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…Membranous occlusion of veins is rare and mostly reported in the suprahepatic inferior vena cava (IVC), resulting in hepatic venous outflow obstruction. Angioplasty by balloon dilations can be a safe and effective treatment for membranous occlusion of IVC (5)(6)(7)(8). Our patient was also relieved by balloon dilation of SCV and recovered successfully.…”
Section: Introductionsupporting
confidence: 50%
“…Concerning the treatment, many studies have shown that angioplasty has excellent immediate and late efficacy in treating membranous obstruction of the IVC (MOVC) (5)(6)(7)(8). A few surgical techniques also exist, but they are less exploited because of the superiority of endovascular treatment for its noninvasive nature and lower morbidity- mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were consecutively admitted in 57 (80.28%) studies 9 , 12 , 14 25 , 28 , 30 39 , 41 45 , 47 – 57 , 59 , 64 , 66 , 68 , 70 75 , 78 83 . Fifty one (71.83%) studies were considered to be of high-quality 9 , 12 , 14 , 16 19 , 21 23 , 25 , 26 , 31 – 34 , 39 , 41 43 , 45 – 47 , 49 56 , 58 , 59 , 61 64 , 66 68 , 70 75 , 78 83 and six (8.45%) studies were of poor-quality 13 , 15 , 29 , 65 , 76 , 77 . The site of obstruction was clearly reported in 53 (75.7%) studies (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, PTA, which is the first-line treatment for stenosis of the hepatic portion of the IVC due to its high efficacy and safety, was performed ( 3 , 17 - 19 ). Restenosis was observed at three months after PTA ( Fig.…”
Section: Discussionmentioning
confidence: 99%